The antibacterial activity of green coffee and Arabica coffee extracts on cariogenic Streptococcus mutans isolated from dental caries: An in vitro study. - Kadhum Bakkir , Lammya (University of Thi-Qar Journal of Science, 2017)
Background: different plant derived substances are widely used in the prevention of dental caries through their activity on Streptococcus mutans which is considered to be major cariogenic bacteria. Aim of the study: The aim of this study was to evaluate the antimicrobial activity of green coffee and Arabica coffee on Streptococcus mutans. Materials and methods: Agar well diffusion method with measurement of inhibition zones of S. mutans were used to assess the antibacterial effect of different concentrations of green coffee and Arabica coffee with or without sugar. Streptococcus mutans bacteria were isolated from dental caries in patients consulted the central dental clinics in Basrah (Al Shaheed Qies center) for treatment. Results: Without sugar Green coffee showed greater inhibitory effect on S. mutans than Arabica coffee. The minimum inhibition zone (0.5cm) was recorded at concentration of ( 1.5g/100ml) in green coffee compared to ( 0.5cm) in Arabica coffee that was obtained only at a higher concentration of (3.5g/100ml) .When sugar was added the antibacterial effect of both Green and Arabica coffee declined significantly leading to minimum inhibition zones of ( 0.7cm) and (0.2cm) at a concentration of ( 3.5g/100ml) for green coffee and Arabica coffee respectively. Boiling of both types of coffee showed no significant alteration in their antibacterial activity as compared to non-boiled preparations. Conclusion: consumption of green coffee without adding sugar might be a promising adjunct in the prevention of dental caries owing to its antimicrobial activity against S. mutans bacteria.